2021
DOI: 10.3389/fmicb.2021.700693
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Compounds in the Volatilome of Social Spider Communities

Abstract: Social arthropods such as termites, ants, and bees are among others the most successful animal groups on earth. However, social arthropods face an elevated risk of infections due to the dense colony structure, which facilitates pathogen transmission. An interesting hypothesis is that social arthropods are protected by chemical compounds produced by the arthropods themselves, microbial symbionts, or plants they associate with. Stegodyphus dumicola is an African social spider species, inhabiting communal silk ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…In our study, we found relatively more nests on Acacia mellifera and Combretum imberbe, which are both known for producing antimicrobial compounds [60][61][62][63]. Alternatively, the host plant could facilitate beneficial conditions for microorganisms that produce antimicrobial compounds or other metabolites beneficial to the spiders [58,59,64]. This poses the interesting question of whether spiders can acquire particular beneficial microbial nest symbionts by choice of host plant, or by integrating specific plant material into the nest.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In our study, we found relatively more nests on Acacia mellifera and Combretum imberbe, which are both known for producing antimicrobial compounds [60][61][62][63]. Alternatively, the host plant could facilitate beneficial conditions for microorganisms that produce antimicrobial compounds or other metabolites beneficial to the spiders [58,59,64]. This poses the interesting question of whether spiders can acquire particular beneficial microbial nest symbionts by choice of host plant, or by integrating specific plant material into the nest.…”
Section: Discussionmentioning
confidence: 68%
“…The S. dumicola nest is made predominantly of silk, into which plant material and sometimes exoskeletons of prey is incorporated, and the nest hosts a unique microbiome [58]. A recent study showed that S. dumicola nests (the actual silk retreat) contain volatile organic compounds with antimicrobial properties, which may protect the spiders against pathogens; many of these volatiles likely originated from the host plants [59]. The nest microbiome and associated volatile compounds are influenced by the local environment, notably by the plants on which the spiders build their nests [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadecane was reported to have antimicrobial activity, anti-HIV, and antioxidants (Kumar et al, 2018). Docosane had displayed antimicrobial activities against Bacillus thuringiensis, Staphylococcus aureus, Escherichia coli, and Candida albicans (Lammers et al, 2021) Heneicosane has been reported to have antimicrobial effect on pathogenic microorganisms. Heneicosane extracted from Plumbago zeylanica was used for measuring the antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, volatiles spread fast in both the gas and water phase [ 26 ]. Via the gaseous phase, volatiles can spread in highly complex ecosystems such as soil [ 27 ], insect nests [ 28 ] and spider nests [ 29 ] and can fulfill functions such as communication [ 30 ] and antimicrobial defense [ 31 ] which cannot be performed by solvents due to the lack of effective spreading.…”
Section: Biochemistry Of Volatiles: Diverse and Diffusivementioning
confidence: 99%